2014
DOI: 10.1002/jbm.a.35186
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell responses in terms of adhesion, proliferation, and morphology to stiffness of polydimethylsiloxane elastomer substrates

Abstract: Extracellular environments can regulate cell behavior because cells can actively sense their mechanical environments. This study evaluated the adhesion, proliferation and morphology of endothelial cells on polydimethylsiloxane (PDMS)/alumina (Al2 O3 ) composites and pure PDMS. The substrates were prepared from pure PDMS and its composites with 2.5, 5, 7.5, and 10 wt % Al2 O3 at a curing temperature of 50°C for 4 h. The substrates were then characterized by mechanical, structural, and morphological analyses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…Such endothelial cells exhibited rounded to more spread morphologies on soft to hard PAAM substrates, respectively. This is in agreement with previously published data on the morphological dependence of endothelial cells on substrate stiffness, where cells showed rounded to more spread resting shapes, as substrate stiffness was increased (Yeung et al 2005;Ataollahi et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Such endothelial cells exhibited rounded to more spread morphologies on soft to hard PAAM substrates, respectively. This is in agreement with previously published data on the morphological dependence of endothelial cells on substrate stiffness, where cells showed rounded to more spread resting shapes, as substrate stiffness was increased (Yeung et al 2005;Ataollahi et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Stiffer substrates cause enhanced cytoskeleton through enrichment of actin structure and generation of new stress fibers (Geiger et al 2001), as an early study suggested that stress fibers represent an increased need for adhesion to the substrate (Sumpio et al 1988). Here, we observed cell stiffening and also enhanced adhesiveness of HUVECs when interacted with stiffer substrates, consistent with a recent study which reported the increased adhesion of endothelial cells with increasing the stiffness of substrates (Ataollahi et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…60 Some authors have noticed that bovine aortic endothelial cells (BAECs) have stronger attachment and increased spreading on stiff (1.1 MPa) vs. soft (0.3 MPa) PDMS substrates. 61 Some authors believe that the effect of a soft substrate on endothelial cells comes from more emphasis on the cell-cell junctions rather than substrate adhesions. This seems to lead to the beginning of more stable vascular networks.…”
Section: Scaffolding Materialsmentioning
confidence: 99%